An early atherosclerotic change detected by an aortic angioscopy in a young patient with coarctation of the aorta: a case report - Nitta, Manabu (J Cardiol Cases, 2020)
The patient was a 19-year-old woman who had experienced headache for 1 year. Soon after birth, ventricular septal defects were diagnosed, the size of which were small, therefore not requiring surgical repair. She also noticed hypertension, with up to 184/110 mmHg of blood pressure. Her physical examination revealed a difference in blood pressure between her upper and lower limbs (160/108 and 92/65 mmHg, respectively). A cardiac computed tomography image clearly demonstrated the narrowing of the aortic isthmus. Coarctation of the aorta (CoA) was definitively diagnosed and was the cause of the upper limb hypertension and headache. Cardiac catheterization revealed 3.8 mm of the aortic isthmus and 65 mmHg of the peak-to-peak pressure gradient across the CoA. The patient was offered endovascular therapy of the CoA. A non-covered stent implantation was successfully performed and the pressure gradient across the aortic isthmus disappeared. Her upper limb hypertension also improved. Aortic angioscopy revealed a yellow plaque on the aortic intima, located proximal to the coarctation site, which was exposed owing to high blood pressure. Our case highlights that an atherosclerotic change can develop even in young patients with hypertension. <Learning objective: An aortic angioscope can detect an early atherosclerotic change of aorta, which other imaging modalities such as computed tomography and intravascular ultrasonography cannot show. An early atherosclerosis can develop even in a young patient with hypertension; therefore, coarctation of the aorta should be diagnosed and treated appropriately as soon as possible.>